Letter to the Editor: The Invasive Caribbean Mytilopsis sallei (Bivalvia: Dreissenidae): A Short Review - Dan Marelli (ASEAN Journal on Science and Technology for Development, 2020)
This letter seeks to comment on the taxonomy of members of the genus Mytilopsis (Bivalvia: Dreissenidae) that are found as invasive species in many Asian estuarine systems.